Stroke in Indigenous Africans, African Americans, and European Americans Interplay of Racial and Geographic Factors - Owolabi, Mayowa; Sarfo, Fred Stephen; Howard, Virginia J.; Irvin, Marguerite R.; Gebregziabher, Mulugeta; Akinyemi, Rufus; Bennett, Aleena; Armstrong, Kevin; Tiwari, Hemant K.; Akpalu, Albert...et.al. (Stroke, 2021)
An article published in Stroke. 2017;48:1169-1175. DOI: 10.1161/STROKEAHA.116.015937